Proses Berpikir Konektif Mahasiswa dalam Membangun Koneksi Matematika pada Pemecahan Masalah Matematika Kontekstual Bertema Maritim - M. Gunawan Supiarmo; Gilang Primajati; Dita Oktavihari (Mandalika Mathematics and Educations Journal, 2025)
Connective thinking is the process of building ideas to solve problems. This happens by connecting concepts and generalizing them to more complex mathematical problems. Connective thinking is also a stage of forming a thinking scheme that links mathematical ideas when building mathematical connections. This study aims to describe students' connective thinking abilities in building mathematical connections in solving contextual problems with a maritime theme. This study uses a descriptive qualitative approach with three student subjects selected based on different levels of ability. The main instrument is three contextual questions with the theme of ship navigation, which are analyzed through four indicators of connective thinking: cognition, formulation, inference, and reconstruction. The results indicate that high-ability students are able to go through all stages of connective thinking thoroughly and logically. Medium-ability students show an incomplete thinking process, while low-ability students experience difficulties at almost all stages. This study emphasizes the importance of contextual problems that integrates conceptual understanding and reflection to develop students' connective thinking abilities.